Подходы нравственно-патриотического воспитания старших дошкольников как основа модернизации казахстанского образования - Кузинёва, Е.Г. (My University, 2013)
The summary:The problems of morally-patriotic education of rising generation are exposed in the article. Many people in post-soviet space experience a difficult crisis period. Changes take place not only in politics and economy but also in consciousness of people.